De-Europeanisation in Turkey: The Case of the Rule of Law. Issue 1 (2nd January 2016) - Saatçioğlu, Beken
Abstract: This article investigates the political dynamics shaping the post-2010 'de-Europeanisation' of Turkey's judicial system, particularly regarding judicial independence and rule of law. The analysis suggests the limits of conventional Europeanisation accounts emphasising causal factors such as European Union (EU) conditionality and the 'lock-in effects' of liberal reforms due to the benefits of EU accession. The article argues that the Justice and Development Party's (AKP's) bid for political hegemony resulted in the reversal of rule of law reforms. De-Europeanisation is discussed in terms of both legislative changes and the government's observed discourse shift.